Sukuk model determinant as funding strategy of Islamic Bank in Indonesia - Muhamad Nafik Hadi Ryandono (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
The Sukuk issued by Islamic banks in Indonesia has high flexibility and is a unique strategy in funding but in its implementation still faces many determinants that need to be identified. This research uses a qualitative approach and the type of research is exploratory with case study method. The research finds seven determinants of sukuk as an alternative source of fundraising. In fact, these 7 determinants are obstacles to the issuance of sukuk, so that Islamic banks in the issuance of sukuk tend to choose to become Special Purpose Vehicle and or as a selling agent of sukuk. If it is related to a special project, the Islamic bank will develop public fund raising with mudharabah-muqayadah contract. The sukuk model that is suitable and sought by investors in Islamic banks is sukuk based on revenue sharing which is partnership contract. It is since partnership sukuk yield reflects business reality and economic cycle so that it is fair for the owner of fund and fund manager.